KEINDAHAN BUNYI AL-QUR’AN: Kajian Fonologi Surah Al-Fatihah - Nabawiya, Fitria Zahrotan (AL ITQAN: Jurnal Studi Al-Qur'an, 2022)
This study presents an analysis of the application of phonological studies  to the beauty of the sound contained in surah al-Fatihah. The focus of this research is on the beauty, harmonization, and musicalization of the Qur'an surah al-Fatihah. Surah al-Fatihah was chosen because it has a unique and interesting language style to be discussed from a phonological perspective. This study uses the theory of phonology, rhythmic and musicality of the Qur'an, as well as the theory of the beauty of sound. This study aims to identify the beauty of the sound of the Qur'an surah al-Fatihah and find out how the process of its formation. The results of this study are the beauty of the sound of Surah al-Fatihah in the form of a combination of vowels and consonants, long and short vowels, consonants, final sound harmony, and the structure of word choice. With the harmonization in the form of harmony of long and short vowel patterns, consonants, punctuation marks, proximity of makhraj, and also the suitability of the pattern of the sound of verse one with the verse will be the reason how the beauty of the sound is formed. The sound of the Qur'an can be said to be beautiful because it is expressed properly and correctly in accordance with the rules of how to read the Qur'an.